DESIGNING STUDENTS' BOOK FOR WRITING IN EFL CLASSROOM: A PROJECT BASED LEARNING ACTIVITIES - Wulandari, Fitri; Bungakasih, Yeyen; Tristiana, Novita Eka; Kurniati, Kurniati (Premise: Journal of English Education and Applied Linguistics, 2023)
The aims of this research are as follows: first, to know the students' need for the teaching material for the writing process; second, to develop the students' book for writing with project-based learning. This research and development are based on the Borg and Gall model development. The subjects of this research are Grade IX students at the Junior High School of Muhammadiyah Pringsewu. The results of this research are as follows: first, the steps of developing a student's book for writing using PjBL at ninth grade JHS of Muhammadiyah Pringsewu research and information are collecting, the planning of the product, and development of students' book. Second, the results of Expert Judgment, English teachers, and student responses showed that overall, students' book obtained an average score of 3.5 with "good" categorized and was declared "feasible" to be used in the writing process. Third, the student book is effective in supporting students' autonomous learning. This research implies that students and teachers can use this book to support the teaching and learning process, especially in teaching writing skills.